The Effect of forest law enforcement governance and trade license on competitiveness of Indonesian wooden furniture in the European Union market - Lubis, M.; Suharjo, B.; Nurmalina, R.; Purnomo, H. (South Asia Management Association, 2018)
In May 2003 the European Union (EU) initiated an action plan (FLEGT - Forest Law Enforcement, Governance and Trade) followed by the issuance of EUTR (European Union Timber Regulation), effective March 2013, which prohibits the entry of illegal timber and timber products into the EU market. Indonesia as one of the exporting countries reacts with the FLEGT-VPA since 2007 where the Indonesia Timber Legality Assurance System (Sistem Verifikasi Legalitas Kayu - SVLK) forms the basis of the agreement andrecognized by the EU through FLEGT licensing of November 15, 2016. This study is intended to examine the effect of licenses on competitiveness of Indonesian wooden furnitureproducts in EU market. The study covers 8 provinces of wooden furniture center in Indonesia. The methods used include interviews, surveys, focus group discussions; involving producers and related institutions. The data obtained were processed and analyzed using Diamond Porter Model. The FLEGT license has increased the competitiveness of Indonesian wooden furniture in facilitating entry into the EU market. However, there are other factors at play such as relatively new nature of FLEGT-VPA and FLEGT licensing, transition period that every major policy process such FLEGT Licenses experience, level of implementation the EUTR as an incentive towards FLEGT-VPA, timber price, quality, availability, technical performance, logistics and fashion trends, especially for furniture retailers. All these factors have implications for the competitiveness of Indonesia’s FLEGT licensed timber in the EU.